Implementation Of High School Tridharma Through Penta Helix Collaboration In Acceleration Of Pollution Control And Damage Of Citarum River Area - anita kamilah (Prosiding Konferensi Nasional Pengabdian Kepada Masyarakat dan Corporate Social Responsibility (PKM-CSR), 2020)
Citarum River is a national strategic river for the welfare of the people at large. However, there has been pollution and environmental damage that has harmed health, social, economic, ecosystem and environmental resources, so that it is called the dirtiest river in the world. Therefore, steps are needed to accelerate pollution control and damage to the Citarum River watershed, by synergizing the penta helix element program including the role of Higher Education through the dharma of community service. The aim is to review the national legal provisions which form the basis for collaboration of the penta helix elements in realizing a clean Citarum, as well as community empowerment programs in support of the clean Citarum. The normative juridical approach method, descriptive analysis research specifications, and qualitative data analysis. The results of the research: (1) Presidential Decree 15/2018 as a breakthrough to synergize the roles and authorities of various related agencies and stakeholders, including universities and support for the synergy of Pentahelix to provide community rights, especially those around the Citarum River, to get a good and healthy living environment; and (2) the program (3RReduce, Reuse, Recycling) and the arrangement of floating net cages is a community empowerment program to accelerate pollution control and damage to the Citarum watershed.